Implementasi Essential Marketing dan Tiktok Marketing Sebagai Upaya Pembekalan Program Metamorpreneur di Seruni Foundation Bandung - Vidyastuti, Heppy Agustiana; Dagustani, Dani (Universitas Ekuitas Indonesia, 2024)
The Seruni Foundation is a philanthropic institution that cares about education, empowerment, humanity, the development of religious facilities and infrastructure, and other social activities. The formation of the Seruni Foundation aims to include an empowerment program for foster children who are currently studying at senior high school or vocational high school so that they can become entrepreneurs according to their interests. This empowerment program is called Metamorphreneur. The results of the community service team's initial observations of the students assisted by the metamorphreneur program were that the marketing knowledge possessed by the students was still weak. The solution provided by the community service team is to provide essential marketing training and TikTok marketing training. The results of the training and mentoring show that prospective entrepreneurs can understand and implement the knowledge gained. Keywords: Essential marketing,TikTok Marketing, Entrepreneur Abstrak Seruni Foundation merupakan lembaga filantropi yang peduli dengan pendidikan, pemberdayaan, kemanusiaan, pembangunan sarana dan prasarana ibadah serta kegiatan sosial lainnya. Dibentuknya Seruni Foundation memiliki tujuan diantaranya program pemberdayaan bagi anak asuh yang sedang menempuh pendidikan Sekolah Menengah Atas/ Sekolah Menengah Kejuruan sehingga dapat menjadi entrepreneur sesuai dengan peminataan/ketertarikannya. Program pemberdayaan ini dinamakan Metamorpreneur. Hasil observasi awal tim pengabdian kepada masyarakat terhadap siswa binaan program metamorpreneur ini adalah masih lemahnya ilmu marketing yang dimiliki oleh para siswa. Solusi yang diberikan oleh tim pengabdian adalah dengan memberikan pelatihan essential marketing dan pelatihan TikTok marketing. Hasil pelatihan dan pendampingan menunjukkan bahwa para calon entrepreneur dapat memahami dan mengimplementasikan ilmu yang didapat. Kata kunci: Pemasaran dasar, TikTok Marketing, Entrepreneur